1960
DOI: 10.1002/1097-4679(196010)16:4<421::aid-jclp2270160425>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

An abbreviated form of the WAIS verbal scale

Abstract: PROBLEM AND METHODThis study investigates the possibility that the Verbal Scale of the WAIS(1) can be abbreviated to effect a considerable saving of time without sacrifice of either reliability or the variety of functions tap ed by the original instrument.The WAIE Verbal Scale records of 100 consecutive patients aged 16 to 72 at the Middletown State Hospital were taken from the files and rescored using selected items for each subtest according to the scheme in Table 1. Every third item waa used on the Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1962
1962
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The use of only "starred" items in the administration of the S-B may also fall into this category (e.g., Birch, 1955;Wright, 1942). Wolfson and Bachelis (1960) sampled items from selected scales to produce a SF for the WAIS Verbal Scale.…”
Section: Methods Of Abbreviationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of only "starred" items in the administration of the S-B may also fall into this category (e.g., Birch, 1955;Wright, 1942). Wolfson and Bachelis (1960) sampled items from selected scales to produce a SF for the WAIS Verbal Scale.…”
Section: Methods Of Abbreviationmentioning
confidence: 99%
“…Scoring times will also differ: some Wechsler subtests are notoriously difficult to score. No evidence is offered on this point, but it is clear that both scoring times and scoring errors could be reduced by judicious choice of subtests and by the use of modified scoring methods (e.g., Blackburn & Benton, 19S7;Carkhuff, 1962;Jastak & Jastak, 1964;Walker, Hunt, & Schwartz, 1965;Wolfson & Bachelis, 1960).…”
Section: Methodological Problemsmentioning
confidence: 99%
“…Using selected subtests, as Rabin (1943) did, is not the only method of abbreviating the original scale, nor is it necessarily the best. Wolfson and Bachelis (1960) observed that that method necessarily limits the variety of mental processes sampled, whereas using selected items on each of the subtests (reducing the length of the subtests rather than their number) could tap the whole variety of functions contained in the original scale. They proposed a short form of the Verbal scale of the Wechsler Adult Intelligence Scale ( WAIS ; Wechsler, 1955) based on that premise, and Satz and Mogel (1962) extended their work to the Performance scale of the WAIS .…”
Section: How To Abbreviate the Original Scalementioning
confidence: 99%
“…Interest in abbreviated forms of the WAIS continues, although the number of publications in this area is moderate. A new approach to the design of short forms was represented in the publication of Wolfson and Bachelis (1960) and in several other reports that followed a similar procedure. The innovation consists of the reduction of the number of items to be administered within subtests, in addition to the reduction of the number of subtests themselves.…”
Section: Short Formsmentioning
confidence: 99%